Reflections on technological advance and participation in South Korea of ​​companies, universities and institutes in R&D - Licona Michel, Ángel (2025)
The technological advance and creation of patents in South Korea is the result of the investment made by companies, universities and institutes that each year increase the amounts of investment in Research and Development (R&D), in 2000 they allocated 2.1 percent of the GDP and in 2021 they reach 4.9, in the same years the number of researchers increased from 159,973 to 586,666, achieving 102,010 and 237,633 patents, positioning itself as the fourth country with the most registrations. The objective of the article is to analyze the technological advancement and creation of patents by South Korea from 2000-2021, showing the participation of companies, universities and institutes in investment in R&D. To support the reflections, a documentary investigation was carried out that will guarantee the selective recovery of different sources to explain the technological advance through investment in R&D and the growth in the number of researchers and patents.